Indikasi Kartel Komunditas Strategis dalam Perspektif Hukum Persaingan Usaha Tidak Sehat (Studi Kajian Perlindungan Hukum) - Parida Angriani (Faculty of Law, Maranatha Christian University, 2016)
In general, the competition was fair, if done honestly but the competition was not always done honestly. The fraudulent acts one of which was the cartel. Cartels were agreements made by businesses to other businesses in similar production to influence prices and production process. The cartel action usually choose products that have strategic value, as well as production of meat and soy. In the production of strategic community such as meat and soy currently were alleged (indication) the occurence of a cartel. To avoid these allegations, to marketing, production businesses must leave the Antimonopoly Law No.5/1999. Where in the legislation there was a ban on cartel action by businesses that contained in Article 11 of the law. However, the setting of the cartel was still considered less clear and complete, because it does not provide clear and unequivocal definition of the cartel as well as the type of the cartel. To avoid the vagueness of the norm government in formulating laws and should be careful and able to provide legal protection of a clear and unequivocal to the consumer to prevent arbitrary actions of businesses.